Repeatability and Reproducibility of Population Viability Analysis (PVA) and the Implications for Threatened Species Management - Morrison, Clare; Wardle, Cassandra; Castley, J. Guy (Frontiers in Ecology and Evolution, 2016)
Conservation triage focuses on prioritizing species, populations or habitats based on urgency, biodiversity benefits, recovery potential as well as cost. Population Viability Analysis (PVA) is frequently used in population focused conservation prioritizations. The critical nature of many of these management decisions requires that PVA models are repeatable and reproducible to reliably rank species and/or populations quantitatively. This paper assessed the repeatability and reproducibility of a subset of previously published PVA models. We attempted to rerun baseline models from 90 publicly available PVA studies published between 2000-2012 using the two most common PVA modelling software programs, VORTEX and RAMAS-GIS. Forty percent (n = 36) failed, 50% (45) were both repeatable and reproducible, and 10% (9) had missing baseline models. Repeatability was not linked to taxa, IUCN category, PVA program version used, year published or the quality of publication outlet, suggesting that the problem is systemic within the discipline. Complete and systematic presentation of PVA parameters and results are needed to ensure that the scientific input into conservation planning is both robust and reliable, thereby increasing the chances of making decisions that are both beneficial and defensible. The implications for conservation triage may be far reaching if population viability models cannot be reproduced with confidence, thus undermining their intended value.